Addressing the Concurrent Access to Smart Objects in Ubiquitous Computing Scenarios - Vieira, Marcos Alves; Carvalho, Sérgio T. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
The increasing number of smart spaces, fostered by the Internet of Things (IoT) and the Web of Things (WoT), as well as the user mobility in these spaces, can lead to smart spaces overlap, where a certain smart object may be used in different smart spaces. This paper presents the use of ModelDriven Engineering techniques to propose: (i) a language to enable the definition of access rules for smart objects and ubiquitous applications; and (ii) an algorithm to process models written in this language, enabling addressing smart objects’ concurrent access issues that might arise from smart spaces overlap. The proposal validation was performed by modeling a ubiquitous computing scenario’s access rules.